Biodiversity of aspergillus, alternaria, cladosporium and curvularia species in the environment of Nawapara (rajim), District – Raipur, Chhattisgarh - RAJU MAHOBIA; SHAILESH KUMAR JADHAV; REKHA PIMPALGAONKAR (International Journal of Pharma and Bio Sciences, 2017)
Fungal bioaerosols always present in the environment are varying from season to season, month to month, day to day and place to place. Environmental conditions play an important role in distribution of bioaerosols. During the present investigation Gravity petriplates method was used for survey of bioaerosols. The sample of bioaerosols was collected twice a month at fortnightly intervals. In the present studies 1197 fungal colonies and 33fungal species of Aspergillus, Alternaria, Cladosporium and Curvulariawereidentified maximum percentage contribution were of Cladosporiumcladosporiodes (22.24%) Followed by Aspergillusniger(21.42%), Aspergillusflavus (17.31%), Aspergillusversicolar (6.74%), Curvulariaclavata (4.83%), Cladosporiumoxysporium (4.10%), Alternariacitri (3.82%), Alternariaalternata (3.09%), Curvularialunata (2,55%), Alternariasp. (0,18%). It was also observed that the Aspergillusflavus, Aspergillusniger, Cladosporiumcladosporiodes, Curvulariaclavata, Alternariaalternata, Curvularialunata, Aspergillussydowii, Aspergillussydowii, Aspergillus fumigates, Aspergillusluchiensis, Cladosporiumoxysporium, Alternariacitrii,were most frequent while Alternariacrassa, Alternariaradicinia, Alternaria and Curvularia species were least frequent fungi.